INFLUENCE OF VIRAL INFECTION ON LATE BLIGHT DEVELOPMENT - Sharma, Sanjeev (Potato Journal, 2018)
Multiplex of diseases is common in potato under field conditions and development of one pathogen is affected by the presence of other pathogens. In the present study, the effect of viruses infection (PVX, PVYo, PVM, PVS), individually and in mixed infection, was studied on development of late blight. Results revealed that development of late blight is affected by virus infection and virus-infected plants had less development of Phytophthora infestans (except PVS) than were healthy ones. Plants infected with PVS enhanced late blight susceptibility (36.30%) while other viruses decreased it. Highest reduction in disease severity (71.48%) was recorded in PVX followed by PVM/PVYo (65.93%) infected leaves. Amount of sporulation was also significantly higher on PVS infected leaves while it was significantly smaller on leaves infected with other viruses.